Research on outsourcing of digital image forensics based on privacy preserving - Bing-wen FENG; Jian WENG; Wei LU (网络与信息安全学报)
The rapid growth of digital image forensics calls for outsourcing digital forensics services to the cloud.It meets the requirement of image content authentication from both the public and organizations.However,it also brings the privacy concerns over the abuse of sensitive information.Based on the research in related fields,a digital forensics cloud platform with privacy preservation was presented.Furthermore,privacy-preserving outsourcing of three types of digital forensics methods,including copy-move detection,source identification and natural image sta-tistic-based tamper detection,were designed.Various future research directions were also discussed.